Deviation control that deteriorates with fixation distance in basic-type intermittent exotropia - Ryota Takada; Akemi Wakayama; Fumi Tanabe; Shunji Kusaka (BMC Ophthalmology)
Abstract Background/aims The clinical assessment of deviation control at near (30 cm or 1/3 m) and far (5–6 m) does not reflect if and how patients’ control changes between these two predetermined test distances. We examine how patients’ control varies at 6 fixation distances between the two clinical test distances of 30 cm and 5 m. Methods The medical records of 48 patients with basic intermittent exotropia (IXT) were retrospectively reviewed. Patients who had visited the Kindai University Hospital between October 2021 and March 2022 without a prior history of treatments except spectacle correction were included. Eye position was examined with refractive correction using the cover test, and 6 fixation distances at 30 cm, 1 m, 2 m, 3 m, 4 m, and 5 m were tested in increasing order. Control assessed at each fixation distance was classified using the Kushner’s method (2019). This study rated the control of a poor or fair level as unfavorable and the control of an excellent or good level as favorable. The distance at which the patient’s control deteriorated was analyzed. Results Of 48, 38 (79%) patients had a favorable baseline control, and 8 of them could maintain a favorable control at all distances. Of the 30 patients who could not maintain the favorable baseline control, 17 (57%) at 1 m, 2 (7%) at 2 m, 6 (20%) at 3 m, 2 (7%) at 4 m, and 2 (7%) at 5 m were observed with a control deterioration. The incidence of control deterioration at 1 m was significantly higher than the incidence at other distances (between 1 and 2, 4, 5 m, p < 0.01; between 1 and 3 m, p < 0.05). Conclusions Deviation control in patients with basic IXT was affected by fixation distance and most likely worsened at 1 m. Assessing control at various fixation distances may provide a more comprehensive understanding of patients’ actual control.